Pengaruh Peer Teaching terhadap Pengetahuan Remaja mengenai Personal Hygiene Sebagai Upaya Pencegahan Penyakit Skabies di Pondok Pesantren Al-Hayatul Islamiyyah Kedungkandang Kota Malang - Nur Addini Najichatul Abida; Dimas Dwi Yoga; Handy Lala (KOLONI, 2026)
Scabies is a health problem that affects approximately 6%–27% of children and adolescents. This disease is caused by an infestation of the Sarcoptes scabiei mite, which is transmitted through skin contact and often occurs in crowded environments such as Islamic boarding schools. According to the World Health Organization, scabies remains a global health problem with millions of cases each year. Prevention of this disease is closely related to personal hygiene behavior. However, adolescents' low knowledge of personal hygiene is a risk factor for increasing scabies cases. Therefore, effective educational methods are needed. To improve adolescent knowledge, a peer teaching method involving peer interaction is used. The purpose of this study was to determine the effect of peer teaching on adolescent knowledge about personal hygiene as a scabies prevention method at the Al-Hayatul Islamiyah Islamic Boarding School. The research method used a quantitative approach with a quasi-experimental design and a pretest-posttest with control group design. A sample of 92 adolescents was divided into treatment and control groups. Data were collected using questionnaires before and after the intervention. Data analysis used the Wilcoxon test because the data were not normally distributed. The results showed a p-value of 0.000 in the treatment group and a p-value of 0.001 in the control group, indicating that both groups experienced an increase in knowledge. However, the increase in the peer teaching group was more significant than in the lecture method. This indicates that the peer teaching method is more effective in increasing adolescent knowledge. Therefore, this method can be used as an alternative health education method in Islamic boarding schools (pesantren). It is hoped that adolescents will be able to improve their personal hygiene practices in their daily lives.